Practical guidance for use of oral semaglutide in primary care: a narrative review. Issue 8 (16th November 2020) - Morales, Javier; Shubrook, Jay H.; Skolnik, Neil
ABSTRACT: As the cornerstone of type 2 diabetes (T2D) management within the community, primary care providers are now faced with the challenge of not only managing diabetes itself, but also preventing hypoglycemia and weight gain associated with intensive disease management, and reducing cardiovascular risk. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are well established as efficacious treatments for T2D, and the safety/tolerability profile of this drug class is well defined. However, despite their beneficial effects, GLP-1RAs are under-utilized, highlighting the need for novel approaches to increase their use in primary care. Oral semaglutide is the first oral GLP-1RA approved for the treatment of T2D, offering glucose lowering and body weight loss, a low risk of hypoglycemia, and no increase in cardiovascular risk. Oral semaglutide represents an additional treatment option for patients not achieving their glycemic goal despite treatment with metformin, either alone or with other hypoglycemic agents. Oral semaglutide has the potential to increase usage of GLP-1RAs in the primary care setting by addressing clinician and patient concerns about injections, and may facilitate earlier initiation of GLP-1RA therapy in T2D. Due to the formulation of oral semaglutide, clinicians need to be aware of specific considerations in order to ensure optimal use. Such considerations include dosing conditions and use of concomitant medications. This article provides practical guidance on the use of oral semaglutide in the primary care setting, based on evidence from clinical studies, including the phase 3a PIONEER program, and the authors' clinical experience.